Western Europe / Susie Ashworth, Dvid Atkinson, Chris Baty, Andrew Bender, Geert Cole, Duncan Garwood, Susie Grimshaw, Kathryn Hanks, Sarah Johnstone, Alex Landragin, Matt Lane, Cathy Lanigan, Leanne Logan, craig MacKenzie, Lisa Mtchell, Sally O'Brien, Josephine, Quintero, Kalya Ryan, Andrew Stone, Rachel Suddart, Dani Valent, Vivek Wagle, David Willett
The essential insider's guide to the region to travel western europe